Risk of malignancy and clinical outcomes of cyst fluid only nodules in the thyroid based on ultrasound and aspiration cytology - Kanematsu, Risa (Diagn Cytopathol, 2019)
BACKGROUND: The number of extensive studies focusing on cyst fluid only (CFO) thyroid nodules is limited, and the risk of malignancy (ROM) in CFO nodules has not been well‐established. Thus, the purpose of this study was to investigate CFO nodules using cytology and ultrasound. In addition, we sought to define the ROM and determine the recommended clinical management of CFO nodules. METHODS: We retrospectively reviewed cytological preparations of 678 nodules that were originally identified as CFO nodules, including conventional specimens in 209 nodules, liquid based cytology (LBC) specimens in 221 nodules, and both conventional and LBC specimens in 248 nodules. Ultrasound reports with representative photographs were also reviewed. RESULTS: Of the 678 CFO nodules, 214 (31.6%) were reclassified into other categories, including non‐diagnostic/unsatisfactory (ND/UNS) except for CFO (n = 15), benign (n = 198), and malignant (n = 1). Conventional preparations (33.5%) were more frequently reclassified than LBC preparations (13.6%; P < .0001). Re‐aspiration for diagnosis was performed for only one calcified nodule. The rates of surgical resection and malignancy were 3.0% and 0.2%, respectively. Based on American Thyroid Association guidelines and the Kuma Hospital ultrasound classification, worrisome sonographic features were identified in 5.8% and 0% of CFO nodules, respectively. CONCLUSION: We propose that CFO nodules should be classified as separate from ND/UNS nodules; they should be categorized as a subtype of benign nodules. However, it is essential that fine‐needle aspiration cytology be performed under ultrasound‐guided real‐time visualization of needle placement in the target nodule in all cases.